O-21 Arts services in hospices across Scotland: Towards a national mapping. (19th November 2022) - Drury, Rachel; Tsiris, Giorgos
Abstract : Background: The importance of the arts and the arts therapies in palliative care is widely recognised (Lee, McIlfatrick & Fitzpatrick, 2021. Palliat Med. 35:1815; Wilson, Bungay, Munn-Giddings, et al., 2016. Int J Nurs Stud. 56:90). Despite their long history in diverse hospice care contexts both nationally and internationally, the arts are often weakly integrated on a service level provision. Consistency and transparency in terms of service delivery, methods and evaluation are some common issues (Hilliard, 2005. Evid Based Complement Alternat Med. 2:173; Tsiris & Hartley, 2014) and currently there are no national overviews or strategic understandings of arts service provision in hospices. Aims: Seeking to explore some of these issues in Scotland, this presentation outlines the findings of an ongoing national survey that aims to offer an initial mapping of arts service provisions in hospices. The survey attempts to document the scope and stability of current arts service provisions, as well as the profile of arts practitioners working in hospices, and it explores issues pertaining to equality, diversity and inclusion. Methods: Mar-May 22: consultation with stakeholders; ethical approval. Jun-Jul 22: online national survey of all hospices in Scotland. Jul-Sept 22: analysis of data. Data will be analysed using descriptive statistics and thematic analysis. Results: It is anticipated that the strategic overview and understanding of hospice arts provision in Scotland provided by this small-scale study will help to contextualise current practice and highlight strengths and gaps in service provision. By offering new knowledge regarding the arts in hospices on a national level, this study will add to existing evidence in the field pointing to implications for interdisciplinary work and policy making (Turton, Williams, Burton, et al., 2018. Palliat Med. 32:559) and it will highlight potential drivers for funding, education and research in the field. Innovation and interest: There is currently no national overview or strategic understanding of hospice arts provision in Scotland: this study represents the first step in addressing this gap and has the potential to connect artists and influence service provision and policy.